2017
DOI: 10.3390/proteomes5040024
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Multiplex Serological Helicobacter pylori Assay on a Novel Microfluidic Assay Platform

Abstract: Infection with Helicobacter pylori (H. pylori) occurs in 50% of the world population, and is associated with the development of ulcer and gastric cancer. Serological diagnostic tests indicate an H. pylori infection by detecting antibodies directed against H. pylori proteins. In addition to line blots, multiplex assay platforms provide smart solutions for the simultaneous analysis of antibody responses towards several H. pylori proteins. We used seven H. pylori proteins (FliD, gGT, GroEL, HpaA, CagA, VacA, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…This study showed that type I H. pylori infection could increase the level of serum PGI, PGII and G-17, possibly because the inflammatory mechanism. The study of H. pylori virulence factors were focused on the gene level, depicting that CagA and VacA gene positive samples have strong correlation with AG and IM, and can better predict AG and IM 32 , 33 . Some studies have found that the invasion ability of H. pylori infection is associated with the middle region of the vacA gene 34 , 35 .…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that type I H. pylori infection could increase the level of serum PGI, PGII and G-17, possibly because the inflammatory mechanism. The study of H. pylori virulence factors were focused on the gene level, depicting that CagA and VacA gene positive samples have strong correlation with AG and IM, and can better predict AG and IM 32 , 33 . Some studies have found that the invasion ability of H. pylori infection is associated with the middle region of the vacA gene 34 , 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the diagnosis of H. pylori infection is carried out by invasive (for example, endoscopy and endoscopic biopsy for histopathology, culture, and rapid urease test) and non-invasive (for example, urea breath tests, stool antigen test, and serological tests) methods 35 . However, the diagnostic preferences are based on the prevalence of H. pylori infection and age-related gastric cancer incidence in each area.…”
Section: Diagnostic Approaches For H Pylori Infecmentioning
confidence: 99%
“…Positive UBT indicates an active H. pylori infection which require treatment or further confirmation with invasive procedures. 7 Therefore, this study aims to describe the Prevalence of Helicobacter pylori infection in adult patients with dyspeptic symptoms in Abdi Waluyo Hospital Jakarta from January 2017 to December 2019, where we tried to confirmed the positive UBT result with morphological images of the gaster by gastroscopy.…”
Section: Introductionmentioning
confidence: 99%